Evaluation of Vitamin B12 Deficiency and Associated Factors in Patients With Systemic Sclerosis. Issue 5 (August 2018) - Tas Kilic, Diler; Akdogan, Ali; Kilic, Levent; Sari, Alper; Erden, Abdulsamet; Armagan, Berkan; Kilickaya, Muhammed; Kalyoncu, Umut; Turhan, Turan; Kiraz, Sedat; Karaahmetoglu, Selma
Abstract : Background/Objective: In patients with systemic sclerosis (SSc) gastrointestinal (GI) involvement, nutritional status and medications may lead to cobalamin (Vit B12) deficiency. We aimed to determine the frequency and the potential causes of Vit B12 deficiency in SSc patients. Methods: We conducted a cross-sectional analysis of 62 SSc patients in a single center in 1 year period. Medical history and physical examination of patients were reevaluated. Data about organ involvements were obtained from hospital file records. The nutritional status of the patients was assessed with Malnutrition Universal Screening Tool (MUST). Vit B12, homocysteine (except in three patients) and Helicobacter Pylori Immunoglobulin G (H. Pylori IgG) levels were measured in all patients. Vit B12 deficiency was considered as serum Vit B12 level <200 pg/mL or being on Vit B12 replacement therapy. Serum Vit B12 levels of the patients were also grouped as low (<200 pg/mL), borderline (200–300 pg/mL) and normal (>300 pg/mL). Plasma homocysteine levels of the patients were classified as elevated (>9 μmol/L) and hyperhomocysteinemia (>15 μmol/L). Mann–Whitney U and Kruskal–Wallis tests were used to compare parameters among the groups. Correlation was tested by Spearman's correlation coefficient. Results: Forty-four (71.0%) patients were defined as Vit B12 deficient; 22 had Vit B12 level <200 pg/mL (four were on Vit B12 replacement therapy) and the remaining 22 had Vit B12 >200 pg/mL and were already on Vit B12 replacement therapy. The percentage of the patients with hyperhomocysteinemia was significantly higher in the group with Vit B12 <200 pg/mL as compared to other groups ( P = 0.004) but only 33.3% (7/21) of the patients with Vit B12 <200 pg/mL had hyperhomocysteinemia. There were no statistically significant differences between patients with and without Vit B12 deficiency regarding age, mean disease duration, MUST scores, mean hemoglobin levels, H. Pylori IgG positivity and organ involvements ( P > 0.05 for all). Conclusions: Vit B12 deficiency is frequent in SSc and has multiple causes. All patients should be monitored for Vit B12 deficiency. The homocysteine levels seem unlikely to be helpful for confirmation of Vit B12 deficiency.